2016
DOI: 10.1097/jom.0000000000000709
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Sleep Health Education and Sleep Disorders Screening Program in Fire Departments

Abstract: Objective: The objective of this study is to compare three methods of administering a sleep health program (SHP) in fire departments. Methods: An An SHP, comprising sleep health education and screening for common sleep disorders, was implemented in eight fire departments using three approaches:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Healthcare organizations can use the study findings to inform organizational initiatives to provide mental health services to nurses. For example, similar to other shift workers, employee assistance programmes should include sleep health education, evaluation, and training for employees, and sleep disorders screening and sleep wellness should be an integral part of employee health services (Barger et al., ; Rajaratnam et al., ; Richter, Acker, Scholz, & Niklewski, . Nursing management should be actively involved in the process of recognizing sleep as an important factor in mental health among nurses and providing screening, education and advice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare organizations can use the study findings to inform organizational initiatives to provide mental health services to nurses. For example, similar to other shift workers, employee assistance programmes should include sleep health education, evaluation, and training for employees, and sleep disorders screening and sleep wellness should be an integral part of employee health services (Barger et al., ; Rajaratnam et al., ; Richter, Acker, Scholz, & Niklewski, . Nursing management should be actively involved in the process of recognizing sleep as an important factor in mental health among nurses and providing screening, education and advice.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional study identified sleep disturbances as a partial mediator in the association between work-family conflict and depressive symptoms among nurses. Future interventions to promote healthy sleep practices should be evaluated for their effectiveness in addressing the impact of work-family conflict on the mental health of nurses.Healthcare organizations can use the study findings to inform organizational initiatives to provide mental health services to nurses.For example, similar to other shift workers, employee assistance programmes should include sleep health education, evaluation, and training for employees, and sleep disorders screening and sleep wellness should be an integral part of employee health services(Barger et al, 2016;Rajaratnam et al, 2011;Richter, Acker, Scholz, & Niklewski, 2010. Nursing management should be actively involved in the process of recognizing sleep as an important factor in mental health among nurses and providing screening, education and advice.…”
mentioning
confidence: 99%
“…Other components of fatigue training may include optimization of schedules or the sleep environment, mindfulness and/or elements of good behavioral health (10)(11)(12)(13)(14)(15). A sleep health education and sleep disorders screening program implemented in firefighters resulted in 42% of focus group participants reporting behavior change, including trying to get more sleep and paying attention to fatigue levels (16). EMS administrators and managers would benefit from learning whether fatigue training improves objective fatigue and fatigue-related risk outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, treatment and prevention approaches specifically tailored for PSP may be necessary. A trial program targeting sleep health was well received among firefighters who reported increased awareness and subsequent lifestyle changes [69]. Proper education and the integration of sleep hygiene training (i.e., comprising educational training sessions on healthy sleep and fatigue countermeasures modelled after existing programs [69]) into basic PSP training courses may be essential to maintain PSP health.…”
Section: Discussionmentioning
confidence: 99%